Do personality traits and demographic characteristics affect Malaysian Chinese entrepreneurs’ leadership effectiveness? A conceptual framework for SMEs - Beh, Kok Hooi (Asian Scholars Network, 2023)
Small and medium-sized enterprises (SMEs) currently face an increasingly challenging business environment, characterized by rapidly changing customer preferences, globalization, intense competition, limited resources, and human resources issues, among others. In this environment, leadership is a critical asset for SME entrepreneurs to align their business resources towards success. Without strong leadership, there can be no grand vision to drive significant business growth. However, the concept of leadership in entrepreneurship suffers from a lack of conceptual clarity, despite substantial growth in entrepreneurial leadership research since the early 1990s. Moreover, there is limited knowledge on whether an entrepreneur's personality traits And personal demographic characteristics influence the effectiveness and style of their leadership. To address these gaps, this paper establishes an integrated conceptual framework to answer the question: “Do personality traits and demographic characteristics influence leadership effectiveness among Malaysian Chinese SME entrepreneurs?" Empirical findings on the proposed relationships in this framework would offer a better understanding and deeper insights into extant studies and emerging trends on entrepreneurial leadership in SMEs, thereby guiding future leadership research and practice.